2011
DOI: 10.1007/s11274-011-0668-8
|View full text |Cite
|
Sign up to set email alerts
|

Removal of nitrate-N by antibiotic exposed bacterial isolates from constructed wetlands

Abstract: Nitrate-N-removing bacterial strains were isolated from a constructed wetland soil treated with three ionophoric antibiotics: monensin, salinomycin and narasin. Five isolates were selected after initial screening for nitrogen removing potential. Nucleotide sequence analysis of the 16S rRNA gene showed that these isolates were highly similar to Bacillus, and Pseudomonas species. The isolates were assessed for their ability to grow in the presence of ionophoric antibiotics. All strains were found to withstand th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…However, several studies have shown that both oxygen and nitrate can function concurrently during respiration irrespective of the availability of oxygen [20,22]. Such a phenomenon is termed as aerobic denitrification and is more prevalent in Gram negative bacteria such as P. aeruginosa [34]. Our results reflect that although static conditions were conducive for denitrification in strain TMR2.13, aeration created favourable conditions for growth of the aerobic culture.…”
Section: Effect Of Benzoate On Denitrificationsupporting
confidence: 51%
“…However, several studies have shown that both oxygen and nitrate can function concurrently during respiration irrespective of the availability of oxygen [20,22]. Such a phenomenon is termed as aerobic denitrification and is more prevalent in Gram negative bacteria such as P. aeruginosa [34]. Our results reflect that although static conditions were conducive for denitrification in strain TMR2.13, aeration created favourable conditions for growth of the aerobic culture.…”
Section: Effect Of Benzoate On Denitrificationsupporting
confidence: 51%
“…Studies were also removed if only nutrient removal was analyzed without the presence of pesticides or antibiotics. For example, analyzed N removal in the presence of antibiotics; thus, the study was retained for further analysis even though the antibiotic removal potential was not specified [43]; however, Jia et al (2021) investigated N removal and poly-3-hydroxybutyrate-co-3hydroxyvalerate/polylactic acid removal in the absence of any pesticides or antibiotics, so this study was removed from further analysis [44]. Review articles were also excluded from the analysis, given that new research on the topic was not conducted; rather, a summary of the existing research was reviewed and/or meta-analysis was completed.…”
Section: Screening and Coding Of Studies Based Upon Eligibility Criteriamentioning
confidence: 99%
“…Review articles were also excluded from the analysis, given that new research on the topic was not conducted; rather, a summary of the existing research was reviewed and/or meta-analysis was completed. From this, there were 181 primary studies used for further analysis [3,16,23,25,30,32,43,. Each study was evaluated to ensure it pertained to wetland treatment of non-point sources.…”
Section: Screening and Coding Of Studies Based Upon Eligibility Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, consideration over contamination with pharmaceuticals have been increasing since these compounds are, also, considered "pseudo-persistent" pollutants due to their continuous insertion in the environment [6]. These even in low concentrations, have the capacity to affect the exposed biota [7], though studies have reported that some of these compounds can be degraded by microbial activity [8,9] or even natural photolysis reactions [10]. However, occasionally the intermediaries generated by these natural routes can be more toxic and persistent in the environment [11].…”
Section: Introductionmentioning
confidence: 99%